Medicare Spending and the Adequacy of Support with Daily Activities in Community-Living Older Adults with Disability: An Observational Study - Wolff, Jennifer L. (Ann Intern Med, 2019)
BACKGROUND: Identifying factors that affect variation in health care spending among older adults with disabilities may reveal opportunities to better address their care needs while offsetting excess spending. OBJECTIVE: To quantify differences in total Medicare spending among older adults with disability by whether they experience negative consequences due to inadequate support with household, mobility, or self-care activities. DESIGN: Observational study of in-person interviews and linked Medicare claims. SETTING: United States, 2015. PARTICIPANTS: 3716 community-living older adults who participated in the 2015 National Health and Aging Trends Study and survived 12 months. MEASUREMENTS: Total Medicare spending by spending quartile in multivariable regression models that adjust for individual characteristics. RESULTS: Negative consequences were experienced by 18.3% of older adults with household disability, 25.6% with mobility disability, and 20.0% with self-care disability. Median Medicare spending was higher for those who experienced negative consequences with household ($4,866 vs. $4,095), mobility ($7,266 vs. $4,115) and self-care disability ($10,935 vs. $4,436) versus those who did not. In regression-adjusted analyses, differences in median spending did not vary appreciably for older adults who experienced negative consequences in household activities ($338: 95% CI: $−768-$1,444) but was greater for those with mobility ($2,309: 95% CI: $208-$4,409) and self-care disability ($3,187: 95% CI: $432-$5,942). At the bottom spending quartile, differences were observed for self-care only ($1,460: 95% CI: $358-$2,561). No differences were observed at the top spending quartile. LIMITATIONS: This observational study cannot establish causality. CONCLUSION: Inadequate support with mobility and self-care activities is associated with higher Medicare spending, especially at the middle and lower end of spending, which creates the possibility that better supporting the care needs of older adults could offset some Medicare spending.